The phylogeny of the BEP clade in grasses revisited: Evidence from the whole-genome sequences of chloroplasts - Wu, Zhi-Qiang; Ge, Song (Molecular phylogenetics and evolution, 2012)
[Display omitted] ► A fully resolved phylogeny of the major lineages of grasses was obtained. ► The (B,P)E hypotheses was strongly supported. ► The diversification of the BEP clade into three subfamilies happened within ∼4MY. ► The short internal branches in BEP clade caused incongruent phylogenies in studies. Despite the considerable efforts to reconstruct the phylogeny of grasses, the relationships among the subfamilies Bambusoideae, Pooideae and Ehrhartoideae in the BEP clade remain unresolved. Here we completely sequenced three chloroplast genomes of representative species from Bambusoideae and Ehrhartoideae and obtained 19 additional chloroplast genome sequences of other grasses from GenBank. Using sequences of 76 chloroplast protein-coding genes from the 22 grass species, we fully resolved the phylogeny of the BEP clade. Our results strongly supported the (B,P)E hypothesis, i.e., Bambusoideae and Pooideae are more closely related than Ehrhartoideae. This result was not biased by systematic or sampling errors and was impervious to phylogenetic methods or model specification. The divergence time estimate suggests that the initial diversification of the BEP clade into three subfamilies happened within a short time period (∼4MY). The presence of these short internal branches may explain the inability of previous studies to achieve a confident resolution of the BEP clade. The combination of the sequences of the entire chloroplast genomes provided sufficient phylogenetic information to resolve the BEP phylogeny fully. These results provide a valuable evolutionary framework for comparative and functional genomic studies using the grass family as a model system.